Everyday life in the segmented city - Perrone, Camilla; Manella, Gabriele; Tripodi, Lorenzo (Research in urban sociology ;, 2011)
This volume of Research in Urban Sociology is composed of a selection of the papers presented at the conference 'Everyday Life in the Segmented City' held in July 2010, Florence. The conference gathered a multiplicity of approaches and points of view dealing with issues of global urbanization. Urbanization is a phenomenon inscribed into the globalization process that has enormous consequences in the transformation of urban space and the everyday life of citizens, and is reflected also in the flourishing of an analytical discourse increasingly transcending the boundaries of established urban disciplines. The progressive extension of the urban domain beyond the limits of the city and across diverse scales has its corollary in the progressive segmentation of the urban dimension along multiple lines of physical, social, economic, cultural and ethnic nature. This volume focuses on the perspective of the everyday to analyze how practices and policy can overcome the spin towards fragmentation and anomie, and reinforce social cohesion for a more just and livable city, endorsing the 'right to the city' as presented by the seminal work of Henri Lefebvre.